Efeito da dieta hiperlipídica e da tintura de Valeriana officinalis no modelo crônico de discinesia orofacial induzida por haloperidol em ratos - Fachinetto, Roselei (2006)
Haloperidol-induced orofacial dyskinesia (OD) is a putative animal model of tardive dyskinesia (TD) whose pathophysiology has been related to an increase in dopamine turnover, reduction in gabaergic neurotransmission and oxidative stress. Schizophrenic patients have been reported to eat a diet higher in fat than the general population and dietary fat intake can lead to an increase in oxidative stress in animal models. Thus, the first objective of this study was to determine if the association of high fat diet ingestion with prolonged haloperidol treatment could alter the OD and lead to oxidative stress in the rat brain (article 1). Haloperidol decanoate administration (38 mg/kg, which is equivalent 1mg/kg/day) monthly for a period of 6 months to rats fed previously with a HF diet caused an increase in OD. Furthermore, haloperidol caused an increase in the levels of lipid peroxidation in striatum and substantia nigra only in rats fed with the HF diet. Another objective of this work was to evaluate the effects of V. officinalis (1% administered in the drink water) in the animal model of OD induced by long-term treatment with haloperidol (article 2). V. officinalis has been widely used to treat insomnia since it posses GABAmimetic and antioxidant properties. Concomitant treatment with V. officinalis did not modify the intensity or prevalence of OD. We did not find any statistical differences among the groups when oxidative stress parameters were evaluated. On the other hand, haloperidol treatment significantly decreased [3H]-dopamine uptake in slices from striatum of rats, an effect unaltered by V. officinalis. The treatment with V. officinalis reduced the locomotor activity in the open field and increased the time spent on open arm in the plus maze test, confirming the anxiolitic effect of V. fficinalis. Taken together, these results indicate that a high fat diet caused a transitory increase in haloperidol-induced OD in rats and this, at least in part, can be related to the haloperidol-induced oxidative stress in brain structures. Our data also suggest that the reduction in dopamine transport can be a possible mechanism related to the maintenance of chronic OD in rats feeding NF diet. Finally, V. officinalis seems not to be efficacious in the reduction of OD in rats.